Gambaran Iklim social Peserta Pelatihan Tata Rias di PKBM - Anisak Wahid (Jurnal Family Education, 2021)
Research is stimulated by his good guidance given by the tutors in the activities of cosmetology at PKBM Ashi-Shifa Pulai Nagari Gaduik the Tilatang Kamang the Agam. Judging from the tutor very establish goog cooperation in carrying out training activities of cosmetology at PKBM. The study aims to see the picture of the social environment in the process of studying cosmetology at PKBM Ashi-Shifa. This type of research is sort of descriptive set of quantitative, with respondents to are listed as a member of the training of makeup. The withdrawal of the sample of saturated (census), where all members of the population as of the respondents. Gathering data using the questionnaire with the analysis of data in the calculation of persentage. The results showed that;(1) visions of the social environment on lerning life skills of makeup in terms of cooperation in studying, (2) visions of the social environment on lerning life skills of makeup in terms of familiarity in learning,(3) visions of the social environment on lerning life skills of makeup in terms of tolerance in learning.